ESPN Thematic Report on Financing social protection – Finland - Olli Kangas; Laura Kalliomaa-Puha (European Commission, 2022)
Finland is a big spender: its social spending as a share of GDP is the second highest in the EU. Until the international crisis of 2008, Finnish social spending was somewhat below EU-28 levels. But because the economic crisis hit Finland more severely than many other member states, its spending increased by more than in the EU-28. By 2017, the spending level in Finland was 32% of GDP (25.1% in 2008).
In Finland, the government’s share of total financing of social spending is higher − and consequently the share of social security contributions is lower − than in most other EU member states. Finland belongs to the ‘Nordic welfare state regime’ with a wide range of free or heavily subsidised services available to all, and a strong reliance on tax financing. The reliance on taxes goes back to the 1950s. Broadly speaking, the Finnish government finances half of social expenditure, while the other half is financed through contributions. Historically, the share paid by employers was more significant. However, over the past two to three decades there has been a clear shift towards increasing employee contributions and relieving the burden on employers.
In the pension sector, two main reform processes have reduced employer contributions. Until 2010, employers financed almost half of the basic National Pension (NP). While the basic pension reform was being prepared, employer contributions were abolished, and since 2015 the government has borne the entire cost of the NP and of the Guaranteed Pension (GP) that was introduced in 2011. The aim of this reform was to revitalise the Finnish economy, which was still suffering as a result of the 2008 crisis.
In the past, employment-related pensions (introduced in 1962) were financed entirely by employer contributions. However, the economic crisis of the 1990s changed that mode of financing. In 1993, the government introduced employee fees to improve the financial situation of employers. The fee was 3% of gross income. In 1994, the government decided that the cost of successive increases in pension contributions would be borne equally by employers and employees. By 2019, the average employee share has risen to 7.05% of gross income and the employer contribution is 17.35% of the payroll. The biggest part of these contributions is used to finance current pensions, while a smaller part is put in a pensions fund. The financial situation of the pension system is relatively stable, but not without challenges. The rapidly ageing population will continually increase all age-related expenses.
Some options to safeguard the sustainability of the pension system are to: increase employment rates in all age brackets; limit early exits from the labour market; postpone retirements; and perhaps increase the pension age faster than is stipulated by the 2017 pension reform. All of these demand changes in the educational system, in the balance between work and family life, in life-long learning, and in the adaptation of working conditions to recognise the special needs of older employees.
The previous centre-right government tried to carry out a reform of social and healthcare services – the biggest single social policy reform in Finland’s history. The aim was to introduce 18 new administrative domains – counties – between the central government and the municipalities. According to the government’s plan, the responsibility for healthcare and social services, including long-term care, would be transferred to the 18 counties. The hope was that the reform would reduce the future expansion in social spending by €3 billion by 2025. However, the reform proposal encountered several constitutional and other legal problems, and was not passed by the parliament. As a consequence, the government resigned on 8 March 2019. Parliamentary elections were due to be held on 14 April 2019. The new government that will be nominated after the elections will have the responsibility for finalising the reform and securing the sustainability of the Finnish welfare state.